Serum active 1, 25(OH)2D, but not inactive 25(OH)D vitamin D levels are associated with cardiometabolic and cardiovascular disease risk in psoriasis. (October 2019) - Playford, Martin P.; Dey, Amit K.; Zierold, Claudia; Joshi, Aditya A.; Blocki, Frank; Bonelli, Fabrizio; Rodante, Justin A.; Harrington, Charlotte L.; Rivers, Joshua P.; Elnabawi, Youssef A.; Chen, Marcus Y.; Ahlman, Mark A.; et al.
Abstract: Background and aims: Vitamin D exists as an inactive 25-hydroxyvitamin D (25(OH)D) in the bloodstream, which is converted to active 1, 25-dihydroxyvitaminD (1, 25(OH)2 D) in target tissues. Cohort studies reporting cardiovascular disease among individuals with low vitamin D are inconsistent and solely measure 25(OH)D. Psoriasis, a chronic inflammatory disease, is a vitamin D deficient state and is associated with increased cardiovascular disease risk. While serum 25(OH)D is routinely measured, we hypothesized that measurement of 1, 25(OH)2 D in psoriasis may perform better than 25(OH)D in capturing cardiovascular risk. Methods: Consecutive psoriasis patients (N = 122) at baseline underwent FDG PET/CT and CCTA scans to measure visceral adipose volume, aortic vascular uptake of FDG, and coronary plaque burden respectively. Blood levels of both 1, 25(OH)2 D and 25(OH)D were measured by chemiluminescence (LIAISON XL DIaSorin, Stillwater, MN). Results: The psoriasis cohort was middle-aged (mean ± SD: 49.6 ± 13.0), predominantly male (n = 71, 58%), in majority Caucasians (n = 98, 80%), and had moderate-to-severe skin disease [psoriasis area severity index score, PASI score, med. (IQR): 5.5 (3.2–10.7)], with almost one-fourth of the cohort on biologic psoriasis therapy for skin disease management (n = 32, 27%) at baseline. Interestingly, serum levels of 1, 25(OH)2 D but not 25(OH)D were found to be inversely associated with visceral adipose, a marker of cardiometabolic risk in fully adjusted models ( β  = − 0.43, p  = 0.026 and β  = −0.26 p  = 0.13). Similarly, we found an inverse relationship between 1, 25(OH)2 D, but not 25(OH)D, and aortic vascular uptake of FDG independent of traditional risk factors ( β  = −0.19, p  = 0.01). Finally, we found that serum 1, 25(OH)2 D, but not 25(OH)D, was inversely associated with non-calcified coronary plaque burden, as measured by CCTA independent of traditional risk factors ( β  = −0.18, p  = 0.03). Conclusions: In conclusion, we demonstrate that low 1, 25(OH)2 D levels were associated with visceral adipose volume, vascular uptake of FDG and coronary plaque burden independent of traditional risk factors, suggesting that 1, 25(OH)2 D may better capture the cardiometabolic risk associated with vitamin D deficient states. Graphical abstract: Image 1 Highlights: Serum 1, 25(OH)2D but not 25(OH)D levels are inversely associated with psoriasis disease severity. Serum 1, 25(OH)2D but not 25(OH)D levels are inversely associated with surrogate markers of cardiovascular risk in psoriasis. Serum 1, 25(OH)2D but not 25(OH)D levels are inversely associated with visceral adiposity in psoriasis. Serum 1, 25(OH)2D but not 25(OH)D levels increase with psoriasis disease improvement.